A relationship between external public debt and economic growth - R. Casares, Enrique (Estudios Económicos de El Colegio de México, 2015)
An endogenous growth model with two goods, tradable (manufacturing) and non-tradable (non-manufacturing) is presented. Domestic technological knowledge is produced only in the tradable sector. This knowledge overflows into the non-tradable sector. The government issues external debt to finance part of its spending on tradable goods. The domestic interest rate equals the world interest rate plus the country risk premium. The country risk depends positively on the level of external public debt. Households can borrow abroad and have an external credit constraint. An inverted U-shaped nonlinear relationship between the external public debt to GDP ratio and the growth rate is obtained in the steady state. There is empirical evidence showing the existence of this non-linearity between public debt and growth, for both developing and developed countries.